Mono- and Biscouplings Using Triarylbismuths for the Atom-Efficient Arylations of Functionalized Furans under Palladium Catalysis - Rao, Maddali L. N.; Awasthi, Dheeraj K.; Talode, Jalindar B. (Synlett, 2012)
Palladium-catalyzed cross-coupling reactions of functionalized bromofurans with triarylbismuths have been described for the atom-economic synthesis of functionalized arylfuran systems. The coupling reactions using triarylbismuths with various 2-bromofurans and 2,5-dibromofuran underwent smoothly to afford the corresponding 2-arylfurans and 2,5-diarylfurans in high yields in a short reaction time (one hour).
Keywords: palladium; triarylbismuths; 2-bromofurans; cross-coupling; arylation